IoT-Based Automatic Control and Monitoring System for Reverse Osmosis Storage Tanks - Wijaya, Merta; I Putu Trisna Hady Permana S.; Putra, Made Adi Paramartha (Jurnal Nasional Pendidikan Teknik Informatika: JANAPATI, 2025)
Reverse Osmosis (RO) is a system designed to purify drinking water, making it safe for consumption. This system uses a semipermeable membrane filter to carry out the purification process. The advantage of the RO system is its ability to produce cleaner water. However, the purified water must be stored first due to the relatively slow production process of RO. Tirta Utama Drinking Water Depot (DAMIU) is one of the depots that provides RO water, but the RO water supply at Tirta Utama DAMIU often runs out due to poor management. This research aims to develop a water storage management tool to be integrated with the RO system at Tirta Utama DAMIU, with the goal of assisting the depot owner in managing water storage. This tool is designed using an ESP32, equipped with ultrasonic sensors to detect water levels, relays to control water pumps, an LCD to display water level information, and a buzzer as an alarm. The tool also has the capability to connect to the Blynk app, allowing the depot owner to monitor water levels via smartphone. To enhance decision-making in water level control, the system incorporates fuzzy logic as a method to interpret sensor readings and control the RO machine and pumps more intelligently, especially under uncertain or fluctuating water conditions.